2013
DOI: 10.30549/opathrom-06-02
|View full text |Cite
|
Sign up to set email alerts
|

The agency of Greek and Roman statues. From Homer to Constantine

Abstract: In the Archaic period the Greeks did not yet conceptualize the difference between a divinity and its statue. Therefore, stories that stressed the agency of statues separate from their divinities must have seemed less strange at that time than when the statues had become independent, so to speak, from their gods or goddesses. The latter started to happen in the transitional period to the Classical era when the well-known triad of divinities—heroes—mortals came into being, and philosophers began to criticize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…We also 50 Thus Simon (1983) 66. On the relationship between gods and their statues, see Bremmer (2013); Pirenne-Delforge (2010); Mylonopoulos (2010) with further bibliography. 51 On the Plynteria, see e.g.…”
Section: The Cambridge Classical Journalmentioning
confidence: 99%
“…We also 50 Thus Simon (1983) 66. On the relationship between gods and their statues, see Bremmer (2013); Pirenne-Delforge (2010); Mylonopoulos (2010) with further bibliography. 51 On the Plynteria, see e.g.…”
Section: The Cambridge Classical Journalmentioning
confidence: 99%
“…I argue that such interpretations overly reduce the meaning of the cult statues and their functioning in antiquity, as presented at the beginning of the paper. We cannot forget that Aphrodite was first of all a goddess, not an ordinary woman; the religious aspect of the functioning of the statue, so important for the ancients, should not be overlooked in the interpretation (Pironti, 2010;Bremmer, 2013). My paper thus showed that an ancient Greek, a follower of the goddess, is unlikely to have separated their gaze from their religious beliefs, given that the Greeks viewed the sculpture as a statue and the goddess at the same time.…”
mentioning
confidence: 99%